An energy-saving, bending sensitive, and self-healing PVA-borax-IL ternary hydrogel electrolyte for visual flexible electrochromic strain sensors. Issue 47 (3rd November 2022) - Liu, Jia-ning; He, Qi; Pan, Ming-yue; Du, Kui; Gong, Cheng-Bin; Tang, Qian
Abstract : A PVA-borax-IL ternary hydrogel electrolyte was developed for visual flexible electrochromic strain sensors to monitor human activity. Abstract : Hydrogel electrolytes (HGEs) with good sensitivity, high conductivity, high transparency, excellent flexibility, and self-healing ability have become a research hotspot in wearable electronic devices, flexible electronic skin, and other fields. However, the development of HGEs with all these advantages remains a challenge; this limits their applications in flexible electrochromic devices, artificial skin, and biomimetic color-changing strain sensors. This study reports a polyvinyl alcohol-borax-ionic liquid (PVA-borax-IL0.3 )-based ternary HGE, which shows these desired characteristics. The PVA-borax-IL0.3 HGE was prepared by a simple one-pot method. The addition of an IL component to PVA-borax endows the obtained ternary HGE with good ionic conductivity and bending sensitivity while maintaining high transparency and self-healing ability of the PVA-borax hydrogel. Based on its excellent performance, the PVA-borax-IL0.3 HGE was used in an electrochromic device with 1, 1′-bis(4-(ethoxycarbonyl)phenyl)-[4, 4′-bipyridine]-1, 1′-diium dichloride as the electrochromic material. This electrochromic device exhibited excellent photoelectric performance including low coloration voltage (−0.6 V), high optical contrast (65.3%), high coloration efficiency (510 cm 2 C −1 ), good cycling stability (decay in Δ T % after 90 000 s (3000 cycles): 6.9%), ultra-low energy consumption (168 μW cm −2 ), and dual-colored electrochromic behavior. A visual flexible electrochromic strain sensor (VFECSS) was fabricated by integrating strain sensing and electrochromic systems. This VFECSS exhibited excellent bending sensitivity and strain response performance, and it could undergo an interactive color change under the external action, which can be used for intuitive and non-invasive monitoring of complex human activities. This novel VFECSS with ultra-low energy consumption is expected to be promising for application in soft electronic skin, information encryption, wearable devices, and other fields.